An Overview of Female Students Knowledge Level at Senior High School 9 Balikpapan Regarding the Use of Analgesic Drugs for Managing Dysmenorrhea - Parwati, Lely; Sulistiarini, Riski (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
Dysmenorrhea is pain in the lower abdomen or pelvis that descends to the inner thighs and back to the feet. This study aims to determine the level of knowledge of female students at SMAN 9 North Balikpapan regarding the use of analgesic drugs in treating dysmenorrhea. The method used is descriptive analytical research with a cross-sectional approach. A total of 232 female students who experienced primary dysmenorrhea were respondents in this study, who were selected using a purposive sampling technique. Data was collected through a questionnaire that measured respondents' knowledge and behavior in using analgesic drugs. The research results showed that as many as 49% of respondents had good knowledge and 74% of respondents also had good behavior regarding dysmenorrhea and analgesic drugs, but there were still deficiencies in appropriate drug use behavior. It is hoped that this research can increase female students' awareness and understanding of the importance of treating dysmenorrhea effectively, as well as the appropriate use of analgesic drugs.